Histo-morphomertic, Histochemical Solidity Ruling of the Small Intestine in Hamsters and Rabbit According to Different Food (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the present study, the histo-morphometric comparison study of small intestine in hamsters and rabbitwas aimed. Ten of clinically healthy animals of both sexes were collected by Al-Simawa city, age rangedbetween 6 month to 1 year, which was estimated according to the dental equation of the animals. The smallintestine was cut and stained alternatively with Hematoxylin and Eosin (H & E) and (Lilles Alchrome stain).The current study aims to discover the structures and measurement of small intestine belonging to theseanimals specifically their histo-morphometric textures. The anatomical studies revealed that small intestineof both animals consists of: duodenum, jejunum and ileum. Histological exam was showed that the wall ofsmall intestine composed of four layers including: mucosa, submucosa, muscularis and serosa and adventitia.The epithelia of villi small intestine were simple columnar cells for each animal.